2004
DOI: 10.1021/np030546+
|View full text |Cite
|
Sign up to set email alerts
|

Bromophenol Derivatives from the Red Alga Rhodomela confervoides

Abstract: Eight new bromophenol derivatives, 2,3-dibromo-4,5-dihydroxybenzyl methyl sulfoxide (1), 4-(2,3-dibromo-4,5-dihydroxyphenyl)-3-butene-2-one (2), 2-(3-bromo-5-hydroxy-4-methoxyphenyl)-3-(2,3-dibromo-4,5-dihydroxyphenyl)propionic acid (3), 2-(3-bromo-5-hydroxy-4-methoxyphenyl)-3-(2,3-dibromo-4,5-dihydroxyphenyl)propionic acid methyl ester (4), 2-phenyl-3-(2,3-dibromo-4,5-dihydroxyphenyl)propionic acid (5), 4'-methoxy-2'',3',3''-tribromo-4'',5',5''-trihydroxydiphenylacetic acid (6), and 3-bromo-5-hydroxy-4-methox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 20 publications
(32 reference statements)
1
63
0
3
Order By: Relevance
“…In this study, the content of phenolic compounds in some of the red algae and in the lichen studied are as high as in brown macroalgae, the microalgal group with the highest reported level of polyphenols (Connan et al 2006, Stengel et al 2011. For example, the content of phenols in the different solvents was 3.2-6.1 mg g -1 DW for Gelidium pusillum, 1.5-4.4 mg g In addition, sulphated phenols and bromophenols have been detected in several species of red macroalgae (Zhao et al 2004). Among the macroalgae, Rhodophyta possess the highest abundance of halogenated phenols (mainly brominated and chlorinated) with antioxidant, antimicrobial, anticancer, antidiabetic, and antithrombotic effects.…”
Section: Discussionmentioning
confidence: 83%
“…In this study, the content of phenolic compounds in some of the red algae and in the lichen studied are as high as in brown macroalgae, the microalgal group with the highest reported level of polyphenols (Connan et al 2006, Stengel et al 2011. For example, the content of phenols in the different solvents was 3.2-6.1 mg g -1 DW for Gelidium pusillum, 1.5-4.4 mg g In addition, sulphated phenols and bromophenols have been detected in several species of red macroalgae (Zhao et al 2004). Among the macroalgae, Rhodophyta possess the highest abundance of halogenated phenols (mainly brominated and chlorinated) with antioxidant, antimicrobial, anticancer, antidiabetic, and antithrombotic effects.…”
Section: Discussionmentioning
confidence: 83%
“…Species belonging to the family of Rhodomelaceae are known for their richness in phenolic compounds, especially bromophenols [24,25]. There are no previous reports of antioxidant activity of aqueous and acetone IPS extracts of G.crassa.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of Zhao et al 52 reported that the neuroprotective effects of sulforaphane in reducing brain damage, brain edema and protective action of retinal pigment epithet. Sulforaphane has been reported to protect cultured neurons against oxidative stress and dopaminergic neurons against mitochondrial toxins.…”
Section: Sulforaphanementioning
confidence: 95%